Measurement of magnetic properties in boiler steel at high temperatures using a U-shaped yoke - Mingxing Cao; Zhigao Zhang; Jian He; Ruifen Hou; Wenjie Gong; Tong Wu (Scientific Reports)
Abstract This paper presents a specially developed system for measuring the magnetic properties of boiler steel based on a U-shaped yoke. The novelty of this system lies in the unique combination of two main features: (1) a compensation method for accurately measuring iron loss and (2) the implementation of ultra-high-temperature measurement conditions. Firstly, a small measurement coil is used to measure the leakage magnetic flux. By subtracting the leakage magnetic flux from the measurement result, precise local magnetic flux compensation is accomplished. And an iron-loss algorithm is then employed to eliminate the influence of the U-shaped yoke. Secondly, a magnetic property measurement method capable of operating at temperatures up to 630 °C is proposed. The specific total loss (P s) is 34.398 W/kg, and the amplitude permeability (U a) reaches 102.04. The influence of the gap between the sample and the U-shaped yoke is preliminarily validated by a simulation model. This measurement system represents the first successful attempt to provide stable and physically accurate results, addressing the requirements for the in-situ detection of material degradation of boiler steel in special equipment.